2016
DOI: 10.1371/journal.pone.0153370
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a National Maternal Morbidity Outcome Indicator in England: A Population-Based Study Using Routine Hospital Data

Abstract: IntroductionAs maternal deaths become rarer, monitoring near-miss or severe maternal morbidity becomes important as a tool to measure changes in care quality. Many calls have been made to use routinely available hospital administration data to monitor the quality of maternity care. We investigated 1) the feasibility of developing an English Maternal Morbidity Outcome Indicator (EMMOI) by reproducing an Australian indicator using routinely available hospital data, 2) the impact of modifications to the indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 34 publications
3
58
0
Order By: Relevance
“…Therefore, more studies are needed to identify composite risk factors of these adverse pregnancy outcomes, as well as the process of collecting these indicators . As a complement to the birth registry‐based perinatal surveillance, routine hospital administration data can be used to generate a composite indicator to monitor trends in maternal morbidity during pregnancy and childbirth, particularly for quality of maternity care …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, more studies are needed to identify composite risk factors of these adverse pregnancy outcomes, as well as the process of collecting these indicators . As a complement to the birth registry‐based perinatal surveillance, routine hospital administration data can be used to generate a composite indicator to monitor trends in maternal morbidity during pregnancy and childbirth, particularly for quality of maternity care …”
Section: Resultsmentioning
confidence: 99%
“…In this situation, composite indicators may be appropriate. For example, a composite maternal morbidity indicator has been proposed using Australian routine hospital data …”
Section: Stage Two: Indicator Development and Evaluationmentioning
confidence: 99%
“…Another example of evaluating the technical specification of an indicator is a recent study that explored whether a composite maternal morbidity indicator developed using Australian routine data could be derived from HES data . This study found that the quality of the relevant HES data meant that 11 conditions that were included in the Australian indicator would have to be excluded from the English indicator.…”
Section: Stage Two: Indicator Development and Evaluationmentioning
confidence: 99%
“…Most notably, in 2011 the World Health Organization (WHO) published a near miss framework, predominantly using organ dysfunction indicators . The WHO framework has been used globally as an approach to monitoring obstetric near misses and improving care, but it has been subject to criticism for being complex to implement, particularly in low and middle income counties …”
Section: Insights From Maternal Deaths Enquiriesmentioning
confidence: 99%
“…In the UK, two further approaches to monitoring severe maternal morbidity or near miss events have been nationally applied. The English Maternal Morbidity Outcome Indicator (EMMOI) was adapted from an Australian tool and has recently been validated in routine hospital data in England . More recently, the Royal College of Obstetricians and Gynaecologists (RCOG), in partnership with the Royal College of Midwives, the Royal College of Paediatrics and Child Health and the London School of Hygiene and Tropical Medicine, have been commissioned by the Healthcare Quality Improvement Partnership to undertake a new National Maternity and Perinatal Audit, and are developing a national monitoring system including severe morbidity in maternity care…”
Section: Insights From Maternal Deaths Enquiriesmentioning
confidence: 99%